The Constitutional Court's Assessment of The Relationship between Religion and The State in The Context of Marriage Law - Yanis, Tryan Zaki Aulia; Muhtadi, Muhtadi (Analisis: Jurnal Studi Keislaman, 2023)
The study of the relationship between religion and the state, especially within the framework of marriage law, is essential in the Indonesian context which has cultural and religious diversity. This research was driven by the need to understand the complexity of the Constitutional Court's interpretation of religious and constitutional principles in regulating marriage. This research is qualitative research and includes normative legal research with a statutory approach. The data analysis method used is content analysis, key decisions of the Constitutional Court which are related to this research. The findings show variations in the Constitutional Court's interpretation of religious and constitutional principles, both emphasizing equality and freedom of religion and strengthening religious norms in marriage laws. The implications of these findings detail the complex dynamics between legal policies, religious values, and constitutional aspects, highlighting the need to maintain a balance between religious principles and the protection of individual rights.